The diagnostic value of endoscopic narrow band imaging in helicobacter pylori gastritis in children - Özgür, Taner; Özkan, Tanju Başarır; Erdemir, Gülin; Özakın, Cüneyt; Yerci, Ömer (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: In this study we aimed to investigate the sensitivity and specificity of Narrow Band Imaging (NBI) in H. pylori gastritis and compare them with those of rapid urease test and urea breath test. Materials and Methods: A hundred sixty-five children who admitted to Uludag University Pediatric Gastroenterology Unit between October 2009-March 2011 with upper gastrointestinal symptoms were consecutively enrolled. During the endoscopy procedure gastric corporeal, antral and fundal images were obtained, afterwards the same areas were visualized with narrow band imaging and images were recorded again. Results: The study included 68 (41.2%) boys and 97(58.8%) girls. The mean age of the patients were 11.88±4.55. Tissue culture positivity and/or histopathological staining for H. pylori was determined in 56 (33.9%) patients (Group 1) and the other patients (n:109, 43.6%) didn’t have an evidence of H. pylori infection (Group 2). Narrow band images have supported H. pylori infection in 56.4%. The sensitivity of narrow band images for determining H. pylori infection was 92.86% (95% CI 82.7-98), specificity was 62.39% (95% CI 52.6-71.5). Conclusion: Our study is the first to show the role of NBI in diagnosing H. pylori infection in children, as well as determining the sensitivity and specificity of the technique. The specificity is low; however, we suggest that the specific mucosal view of H. pylori gastritis provided by NBI is useful for identifying the areas from which the biopsies should be taken. Moreover, by using this technique, treatment of H. pylori infection may be initiated immediately without performing rapid urease test and without waiting for histopathology report and tissue culture.